Sodium Cholate‐Based Active Delipidation for Rapid and Efficient Clearing and Immunostaining of Deep Biological Samples (Small Methods 1/2022). Issue 1 (18th January 2022) - Na, Myeongsu; Kim, Kitae; Oh, Kyoungjoon; Choi, Hyung Jin; Ha, ChangMan; Chang, Sunghoe
Abstract : Front Cover In article number 2100943, Chang and co‐workers developed a novel sodium cholate‐mediated tissue clearing method, called SCARF. By adopting an ion‐conductive film as the separation barrier, SCARF renders orders of magnitude faster tissue transparency and better immunostaining capability than conventional SDS‐based methods. Thus, SCARF would greatly facilitate the 3D structural mapping of biological tissues in various clearing regimes.